2014
DOI: 10.1002/cbin.10223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of downregulation of ZEB1 on vimentin expression, tumour migration and tumourigenicity of melanoma B16F10 cells and CSCs

Abstract: Zinc-finger E-box binding homeobox 1 (ZEB1) is a master regulator of epithelial-mesenchymal transition (EMT) and has been implicated in primary epithelial cancer biological processes, such as invasion and metastasis. However, the role of ZEB1 in progression of melanoma and cancer stem cells (CSCs) remains obscure. In this study, the recombinant plasmids of t3 shRNAs targeting mouse ZEB1 were constructed and transfected into melanoma B16F10 cells. The stable transfected cells were selected and the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 30 publications
2
19
0
2
Order By: Relevance
“…Probably as a result of the reduced expression of EMT associated genes, cells with CHKα suppression exhibit fewer phenotypic properties of mesenchymal cells, since we detected significantly reduced invasiveness and clonogenicity in shCHKα cells (Figure 6). Concisely, ZEB1, ZEB2, and TWIST1 have all been described to promote invasion, and clonogenicity in GBM and other tumors [12, 4348]. Additionally we found increased CHKα expression on the infiltrative leading edge of GBMs as compared to tumor parenchyma, indicating CHKα expression is associated with invasive properties of the tumor cells in GBM patients (Supplementary Figure S3).…”
Section: Discussionsupporting
confidence: 61%
“…Probably as a result of the reduced expression of EMT associated genes, cells with CHKα suppression exhibit fewer phenotypic properties of mesenchymal cells, since we detected significantly reduced invasiveness and clonogenicity in shCHKα cells (Figure 6). Concisely, ZEB1, ZEB2, and TWIST1 have all been described to promote invasion, and clonogenicity in GBM and other tumors [12, 4348]. Additionally we found increased CHKα expression on the infiltrative leading edge of GBMs as compared to tumor parenchyma, indicating CHKα expression is associated with invasive properties of the tumor cells in GBM patients (Supplementary Figure S3).…”
Section: Discussionsupporting
confidence: 61%
“…On immunoblots, the downregulation of IGF-1 was associated with higher levels of the epithelial marker E-cadherin, and lower levels of the mesenchymal marker N-cadherin (Figure 3A). Levels of zinc finger E-box-binding protein 1 (ZEB1), a major driver of the EMT process in melanoma cells [2830], were also significantly lower in the C10 clone (Figure 3A). These results were supported by flow cytometry analysis, which showed markedly lower levels of the mesenchymal markers CD29, CD44 and CD105 in the C10 clone than in control and parental cells (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Our results show that IGF-1 plays a critical role in EMT in B16-F10 cells. Indeed, IGF-1 downregulation resulted in morphological changes, an upregulation of epithelial marker expression, and a downregulation of mesenchymal markers (N-cadherin, CD29, CD44 and CD105) and ZEB1, which is essential for EMT induction in B16-F10 cells [2830]. Indeed, one of the roles of ZEB1 is to regulate the expression of E-cadherin, a key molecule in the maintenance of epithelial cell characteristics [45], as its loss may enhance the invasive and metastatic behavior of melanoma cells [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidences indicated that ZEB1 closely related with the biological behaviors of tumors, such as invasion and metastasis, stemness of cancer stem cells, tumor angiogenesis and chemosensitivity, which largely contributes to tumors initiation and progression (12,13,(31)(32)(33). Several miRNAs also had been showed to take part in ZEB1 regulation, and therefore adjusted of its function in occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%